2013
DOI: 10.1371/journal.pone.0076928
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Characteristics of Blood Natural Killer Cells from Melanoma Patients at Different Clinical Stages

Abstract: Melanomas are aggressive skin tumors characterized by high metastatic potential. Immunotherapy is a valuable alternative for metastatic melanoma patients resistant to chemotherapy. Natural Killer (NK) cells are efficient anti-tumor cytotoxic effectors. We previously showed that blood NK cells from stage IV metastatic melanoma patients display decreased NK receptors and that chemotherapy modifies the functional status of blood NK cells. To investigate the role of NK cells along melanoma progression, we have her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 41 publications
(44 reference statements)
9
51
2
2
Order By: Relevance
“…4C right panel). These data are in accordance with our previous work describing a correlation between NKp46 expression and duration of stage IV in metastatic patients 15 indicating the importance of NKp46 in melanoma evolution.…”
Section: Impact Of Expression Of Nkp30 Isoforms and Nkp46 Transcriptssupporting
confidence: 93%
See 2 more Smart Citations
“…4C right panel). These data are in accordance with our previous work describing a correlation between NKp46 expression and duration of stage IV in metastatic patients 15 indicating the importance of NKp46 in melanoma evolution.…”
Section: Impact Of Expression Of Nkp30 Isoforms and Nkp46 Transcriptssupporting
confidence: 93%
“…These results confirmed and further strengthened our previous data showing an impact of NKp46 expression at the surface of blood NK cells on the duration of stage IV in melanoma patients. 15 Interestingly, our data show that NKp30A expression level isoform (NK cell fitness) was elevated in rare LS patients that have controlled a metastatic disease. These LS are characterized by unique polymorphisms and isoforms proportions of NKp30.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In nearly all the reports, NK cells were underrepresented in the inflammatory infiltrates, 24 except in colorectal carcinoma 25 and in GIST 11 where they mostly resided in the peri-tumoral areas. 11,26,27 NK cell functions were also seen to be repressed in tumor beds in breast and lung malignancies, due to a downregulation of their natural cytotoxic receptors. 26,28,29 Hence, in most malignancies, NK cell abundance in TILs fails to correlate with clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown no differences in NKG2D expression between peripheral blood mononuclear cells (PBMCs) and LN NK cells in melanoma patients and healthy individuals. [33][34][35][36] However, these studies did not examine the NKG2D expression in tumor infiltrating NK cells. We observed significantly lower NKG2D expression in the intratumoral NK cells, but no difference in the splenic population, between naive and tumorbearing mice.…”
Section: Cd11bmentioning
confidence: 99%